Comparison of ELISA and HPLC-MS methods for the determination of exenatide in biological and biotechnology-based formulation matrices - Pinho, A (2019)
The development of biotechnology-based active pharmaceutical ingredients, such as GLP-1 analogs, brought changes in type 2 diabetes treatment options. For better therapeutic efficiency, these active pharmaceutical ingredients require appropriate administration, without the development of adverse effects or toxicity. Therefore, it is required to develop several quantification methods for GLP-1 analogs products, in order to achieve the therapeutic goals, among which ELISA and HPLC arise. These methods are developed, optimized and validated in order to determine GLP-1 analogs, not only in final formulation of the active pharmaceutical ingredient, but also during preclinical and clinical trials assessment. This review highlights the role of ELISA and HPLC methods that have been used during the assessment for GLP-1 analogs, especially for exenatide.